2019
DOI: 10.1039/c9cp04865k
|View full text |Cite
|
Sign up to set email alerts
|

Study of odd–even effects in physisorption and chemisorption of Ar, N2, O2and NO on open shell Ag11–13+clusters by means of self-consistent van der Waals density functional calculations

Abstract: Electronic and structural odd-even effects in the adsorption of small molecules on open shell silver cationic clusters have been rationalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
(130 reference statements)
1
3
0
Order By: Relevance
“…We compare the binding energy differences of CO and O 2 on pure Ag n + clusters and CO on Ag n O + clusters in Figure . We found that the closed-shell Ag 7 + and Ag 9 + clusters have low reactivity toward O 2 , in good agreement with a previous study . Meanwhile, all Ag n + clusters are reactive to CO, which are different from the negatively charged Ag n – clusters that were reported as inert toward CO .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We compare the binding energy differences of CO and O 2 on pure Ag n + clusters and CO on Ag n O + clusters in Figure . We found that the closed-shell Ag 7 + and Ag 9 + clusters have low reactivity toward O 2 , in good agreement with a previous study . Meanwhile, all Ag n + clusters are reactive to CO, which are different from the negatively charged Ag n – clusters that were reported as inert toward CO .…”
Section: Resultssupporting
confidence: 91%
“…clusters have low reactivity toward O 2 , in good agreement with a previous study. 46 Meanwhile, all Ag n + clusters are reactive to CO, which are different from the negatively charged Ag n − clusters that were reported as inert toward CO. 47 However, the low activity of closed-shell Ag n + clusters toward O 2 makes them unsuitable for CO oxidation. Therefore, it is necessary to add atomic O species in Ag n + clusters to provide new active sites and even alter the reaction mechanism.…”
Section: Calculation Of Co Oxidation On Agmentioning
confidence: 91%
“…As advised in the bibliography concerning the adsorption of small molecules on Ag n clusters, a dispersion-corrected functional was used, i.e. , the optB86b-vdW functional .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Silver clusters are ideal model systems to study the active sites of silver-based catalysts and several theoretical concepts, and have been intensively studied. [7][8][9][10][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] The mass spectrometry experiments revealed an odd-even oscillation of the abundances of Ag n + , in which the odd sizes with an even number of valence electrons are more abundant than their neighbors. 39 In addition to the odd-even oscillation trend, the ion intensities decrease sharply after the sizes of n = 3, 9, and .…”
Section: Introductionmentioning
confidence: 99%